Land Procurement Rights for Development for Public Interest - Mohammad Roesli; Made Warka; Sri Setyadji; Endang Prasetyawati (Technium Social Sciences Journal, 2021)
This research is a normative research. The essence of land acquisition for the public interest is carried out based on several aspects, namely ontological aspects (teachings about essence), axiological aspects (teachings about values), epistemological aspects (teachings about knowledge), and teleological aspects (teachings about goals). All of them must be in accordance with the 1945 Constitution of the Republic of Indonesia and be stated in the Land Acquisition Law aimed at creating a just, prosperous and prosperous society based on Pancasila and the 1945 Constitution of the Republic of Indonesia, the government needs to carry out development, to ensure the implementation of development.